"We have our own struggle": Up Against the Wall Motherfucker and the avant-garde of community action, the Lower East Side, 1968. Issue 1 (2nd January 2016) - Hannan, Conor
Abstract: This article examines the activist method and motivation of Up Against the Wall Motherfucker (UAW/MF), an art-political collective formed on the Lower East Side in the late 1960s. Exploring a series of actions, organizational alliances and community-orientated programs, it argues that the group's project was informed by a critique of the social and political disengagement of postwar American art practice. In examining these themes within their neighborhood context, the paper makes an ancillary argument for addressing the local within histories of the radical American 1960s. While 1968 stands as a symbolic moment of political and social upheaval, the actions of UAW/MF – and its forbearer, Black Mask – illustrate the local dimensions of the so-called "protest era, " and highlight anxieties and concerns that promoted social revolt at the grassroots level.